Virtual resource allocation method with the consideration of performance interference among virtual machines - Lei YANG; He-xu XING; Yu DAI; Sai XU; Hao WANG; Bin ZHANG (Tongxin xuebao)
A method for allocating the virtual resource with the consideration of the performance interference among vir-tual machines was proposed.The model for evaluating the performance interference among virtual machines was formed and the method for predicting the performance interference was presented based on the workload pattern of the virtual machine.The predicted result of the performance interference among virtual machines was put into the evaluation of the resource allocation plan to be used as the basis for resource allocation.By doing this,the effectiveness of the resource al-location plan could be insured.The experiments show that the proposed virtual resource allocation method can insure the execution performance of the application deployed on the virtual machines.